Trading up the happiness ladder - Barbara Dluhosch; Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2012)
How globalization affects happiness is highly disputed. Several studies use an index that amalgamates globalization's different dimensions into a single variable. Unlike previous studies and in order to better illuminate its facets, we adopt a disaggregated perspective on trade (policy) data. Distinguishing actual trade flows and the option value of trade, we find the former to slightly depress happiness, the latter to significantly promote happiness. Segmentation of WVS-data shows that the positive connotation is concentrated in low-income countries still in the process of climbing the income ladder, thus backing the notion of a shift in values.
urn:nbn:de:gbv:705-opus-29648
Keywords: F13; I31; 330; Happiness; Well-Being; International Trade